Problems and Countermeasures of Rural Public Management under the Perspective of Rural Revitalization - Chen, Junsheng (Journal of Global Economy, Business and Finance, 2025)
In order to deeply understand the challenges and countermeasures of rural public management under the background of rural revitalization, the method of theoretical discussion is adopted to deeply analyze the significance, problems and causes of rural public management. It is found that the unreasonable allocation of public resources, the outdated social governance model and the lack of grassroots governance capacity are the main problems of the current rural public management. This paper puts forward countermeasures and suggestions for optimizing resource allocation, innovating governance mode and strengthening grassroots governance capacity, so as to improve the level of rural public management and promote the healthy development of rural revitalization.